Estudo da eterificação catalítica de glicerol em produtos de alto valor agregado com o uso de reator contínuo e pressões variadas - Marinho, Carolina Messias (2021)
The huge amount of glycerol obtained during the production of biodiesel has led to several research around the world in search of better use of this by-product. Glycerol etherification is a promising alternative that enables the use of products as fuel additives and various intermediates in the chemical industry. The objective of this work was to study the etherification of glycerol with ethanol using Amberlyst 15 and Zeolite Beta catalysts in a fixed bed reactor. We analyzed through a four-factor central composite design the influence of independent process variables including pressure (7-10.3 MPa), temperature (180-370 ºC), ethanol/glycerol molar ratio (4-30/1) and amount of catalyst (0-0.95 g). Special interest was taken in evaluating the effect of pressure, since this reaction mixture can be one or two phases depending on this variable associated with the ethanol/glycerol molar ratio and temperature. The reactions developed with Amberlyst 15 resulted in a maximum of 97% for glycerol conversion (269 ºC, 12:1 ethanol/glycerol molar ratio, 0.78 g catalyst and 2.5 MPa) and in terms of yield in ethers, the optimization study using canonical analysis led to an optimal value of 69% (242 ºC, ethanol/glycerol molar ratio of 22:1, 0.63 g of catalyst and 7.1 MPa). The experimental runs carried out with Beta Zeolite showed a maximum conversion of 83% and an optimum ether yield of 50% under the same experimental conditions (319 ºC, 25:1 ethanol/glycerol molar ratio, 0.69 g of catalyst and 7.9 g MPa). The results indicated the feasibility of the process of glycerol etherification with ethanol in a fixed bed reactor. Furthermore, they also demonstrated that it is not necessary to keep all reagents only in the liquid phase to minimize the effects related to mass transfer and obtain good results.